Neurosecretory Protein GL Induces Fat Accumulation in Chicks - Shikano, Kenshiro; Iwakoshi-Ukena, Eiko; Kato, Masaki; Furumitsu, Megumi; Bentley, George E.; Kriegsfeld, Lance J.; Ukena, Kazuyoshi (Frontiers in Endocrinology, 2019)
We recently found a previously unidentified cDNA in chicken hypothalamus which encodes the precursor for neurosecretory protein GL (NPGL). A previous study showed that intracerebroventricular (i.c.v.) infusion of NPGL caused body mass gain in chicks. However, it was not clear which part(s) of the body gained mass. In the present study, we investigated which tissues increased in mass after chronic i.c.v. infusion of NPGL in chicks. We found that NPGL increased the masses of the liver, abdominal fat, and subcutaneous fat, while NPGL did not affect the masses of muscles, including pectoralis major, pectoralis minor, and biceps femoris. Oil Red O staining revealed that fat deposition had occurred in the liver. In addition, the size of the lipid droplets in the abdominal fat increased. Furthermore, we found an upregulation of lipogenesis and downregulation of lipolysis in the abdominal fat, but not in the liver. These results indicate that NPGL is involved in fat storage in chicks.